2016
DOI: 10.1063/1.4960102
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional boron: Lightest catalyst for hydrogen and oxygen evolution reaction

Abstract: The hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) have been envisaged on a two-dimensional (2D) boron sheet through electronic structure calculations based on a density functional theory framework. To date, boron sheets are the lightest 2D material and, therefore, exploring the catalytic activity of such a monolayer system would be quite intuitive both from fundamental and application perspectives. We have functionalized the boron sheet (BS) with different elemental dopants like car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 45 publications
3
67
0
1
Order By: Relevance
“…In a recent study, Ba et al experimentally synthesized such type of sheets where they trimmed down the band gap of h-BN sheet to � 2 eV which is about 1/3 of pristine sheet. [41] Now, considering the influence of ASA on the band gap of GRAP, BCN, and h-BN, we found that ASA adsorbed GRAP and BCN sheet do not show any change in the band structure, as the ASA flat bands occur deep in the conduction and valence band. A negligibly small increase of 9 meV (11 meV) in the band gap was seen in ASA adsorbed BCN1 (BCN2) for C1 configuration.…”
Section: Electronic Structurementioning
confidence: 75%
See 1 more Smart Citation
“…In a recent study, Ba et al experimentally synthesized such type of sheets where they trimmed down the band gap of h-BN sheet to � 2 eV which is about 1/3 of pristine sheet. [41] Now, considering the influence of ASA on the band gap of GRAP, BCN, and h-BN, we found that ASA adsorbed GRAP and BCN sheet do not show any change in the band structure, as the ASA flat bands occur deep in the conduction and valence band. A negligibly small increase of 9 meV (11 meV) in the band gap was seen in ASA adsorbed BCN1 (BCN2) for C1 configuration.…”
Section: Electronic Structurementioning
confidence: 75%
“…In a recent study, Ba et al. experimentally synthesized such type of sheets where they trimmed down the band gap of h‐BN sheet to ≈2 eV which is about 1/3 of pristine sheet …”
Section: Resultsmentioning
confidence: 99%
“…23 These novel properties make borophene an ideal candidate for various applications. 9 Ab initio studies predicted that doped borophene can be used as a catalyst for hydrogen and oxygen evolution reactions, 24 is a promising anode material for lithium-ion batteries, 25,26 and is a potential hydrogen storage medium. 27 Boronbased microelectronic device applications is an another interesting field, however, the implementation of borophene requires further investigation.…”
mentioning
confidence: 99%
“…The free energy of the adsorbed hydrogen is defined as DG H* ¼ E ads þ DE ZPE À TDS H (H* is the adsorbed phase of hydrogen on the surface), where E ads is the adsorption energy of hydrogen and DE ZPE is the zero point energy (ZPE) difference of H 2 in adsorbed and gas state, which is around 0.04 eV. [23][24][25] The entropic contribution differencef or the adsorbed hydrogen is the third term of the equation,w hichgives rise to ac orrection value of 0.2 eV under the experimental conditions. The adsorption entropy DS H %À 1 2 DS 0 H assuming the vibrational entropy is small in the adsorbed state with DS 0 H is the entropy of H 2 in gas phase.T he free energy corresponding to the adsorp- Table 1.…”
Section: Resultsmentioning
confidence: 99%